2011
DOI: 10.2147/jmdh.s21385
|View full text |Cite
|
Sign up to set email alerts
|

Self-care and anticipated transition into retirement and later life in a Nordic welfare context

Abstract: Few studies have appeared in the health care literature on the meaning of transition into retirement and later life. However, this predictable-involuntary transition may influence personal health and well-being, and studying it from a self-care perspective could be useful. The aim of this study was to illuminate aspects of self-care in a group of middle-aged individuals in relation to their anticipated transition into retirement in the Nordic welfare context. A total of 13 individuals, aged 55 to 65 years, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…In line with previous research [23], the process towards early retirement appeared to be multi-factorial and was frequently not determined by one single factor. This suggests that interventions and policies should not focus on one factor but integrate measures on a combination of relevant factors.…”
Section: Discussionsupporting
confidence: 88%
“…In line with previous research [23], the process towards early retirement appeared to be multi-factorial and was frequently not determined by one single factor. This suggests that interventions and policies should not focus on one factor but integrate measures on a combination of relevant factors.…”
Section: Discussionsupporting
confidence: 88%
“…At the same time, they valued such activities for their health and well-being, and being active, both socially and physically, could stimulate the appetite. A consciousness of the benefit of activities for maintaining health and well-being in later life has also been reported in other studies 31,38. Along with health problems and limited mobility, external factors, like slippery roads, could also influence the performance of such activities negatively.…”
Section: Discussionsupporting
confidence: 63%
“…A study on the transition into retirement and later life in a Nordic welfare context41 showed that the informants, aged 56–65 years of age, looked forward to retirement when they would be free and motivated to be active or even get a new job. In a study by Dale et al,9 the sense of being useful to other people is emphasized, as well as taking care of grandchildren.…”
Section: Discussionmentioning
confidence: 99%